The (hidden) financial flows of terrorist organizations: A literature review and some preliminary empirical results - Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2010)
In this paper the financial means of international (mostly Islamistic) terror organizations are analysed. First, some short remarks about the organization of international terror organizations are made. Second and in a much more detailed way a literature review is provided about the financing of terrorist and organized crime organizations, their sources and the various methods they use. Third, a first attempt is made to estimate the financial means of terror organizations with the help of a latent estimation approach (MIMIC procedure). The figures show that Al Qaeda and other terror organizations have sufficient financial means. Third, some remarks are made about the negative effects of terror on the economy in highly developed countries and some strategies are presented to combat the financing of terrorism.
Keywords: K42; H56; O17; 330; Financial flows of terrorist organizations; Hawala banking; money laundering; organized crime; kinds of terrorist financing; Organisierte Kriminalität; Umsatz; Schätzung; Politische Gewalt; Islamisch; Internationale Finanzierung; Kapitalmobilität; Geldwäsche; Islamische Bank; Welt